Contribution of Platelet-derived Factor Va to Thrombin Generation on Immobilized Collagen- and Fibrinogen-adherent Platelets - Briedé, Jacob J.; Heemskerk, Johan W. M.; Cornelis van’t, Veer; Hemker, H. Coenraad; Lindhout, Theo (Thrombosis and Haemostasis, 2001)
Adhesion of platelets to immobilized collagen induces the expression of anionic phospholipids, e. g. phosphatidylserine (PS), in the outer leaflet of the plasma membrane of these platelets. In contrast, of the platelets that adhere to immobilized fibrinogen only a small sub-population representing 10 ± 3% of the total population of the fibrinogen-adherent platelets has exposed PS as probed by annexin V binding. Although the presence of PS is thought to be critical for thrombin generation at the platelet surface, no information is available about the effect of this differential PS exposure on the ability of adherent platelets to support thrombin generation. Perfusion of the fibrinogen- or collagen-adherent platelets with solutions containing factor Xa and prothrombin resulted in thrombin generation that i) increased linear during the first perfusion minutes, ii) was about two-fold faster at collagen-adherent than at fibrinogen-adherent platelets and iii) was for more than 98% restricted to the surface of the adherent platelets. It appeared that the lower thrombin generating capacity of fibrinogen-adherent platelets is not due to a lower overall surface density of PS, but is caused by lower amounts of platelet-bound factor Va. Firstly, in both cases thrombin generation could be completely attenuated with antibodies against human factor Va, and secondly, in the presence of an excess of exogenous plasma-derived factor Va similar initial rates of thrombin formation were measured for collagen- and fibrinogen-adherent platelets. Our findings suggest a unique role for immobilized collagen in maintaining haemostasis.
Keywords: Fibrinogen; collagen; platelets; platelet factor V; prothrombinase